The REPELATION POTENCY OF N-HEXANE EXTRACT OF BASIL LEAF AND STEM (OCIMUM BASILICUM L.) AGAINST CULEX QUINQUEFASCIATUS - Ramayanti, Indri Ramayanti; Dwi Hartanti, Miranti; Aulia Rahman, Reynaldi (International Journal of Islamic and Complementary Medicine, 2021)
The Culex quinquefasciatus mosquito is the main vector of filariasis and a popular effort to control it in society is by using chemical materials, but they cause toxic effects in humans, so it is necessary to use a repelant from natural ingredients, one of which is basil containing essential oils and proven to be effective as a repelant against mosquito. The objective of this research was to determine repelant power of n-hexane extract of basil leaves and stems against the Culex quinquefasciatus. This study was a laboratory experimental study using a completely randomized design, with 3 replications at 7 time intervals. The extract concentrations were 15%, 25%, 35 % and ethanol negative control 96%, the positive control repelant X containing 13% DEET. The results showed that the n-hexane extract of basil leaves and stems for 6 hours at a concentration of 15% was able to resist 75% of mosquito, a concentration of 25% was able to resist as much as 85.05%, and a concentration of 35% was able to resist as much as 92.51%, the one-way ANOVA analysis showed that the value of p = 0.000 (p<0,05), meaning that there was a difference in the number of Culex quinquefasciatus perching on the black cloth at various concentrations of n-hexane extracts of leaves and stems of basil, while the probit analysis showed that the effective extract concentration at 90% was 31.52%. The extract of n-hexane leaves and basil stems was effective as a repelant against the Culex quinquefasciatus.